Students' Adaptive Reasoning in Solving Pythagoras Theorem Problems Viewed by Gender - Ahsana Fitri, Khaluka; Prabawanto, Sufyani; Cahya Mulyaning, Endang (KnE Social Sciences, 2024)
Adaptive reasoning is one of the mathematical proficiency strands that refers to the capacity to reflect, explain, justify, and think logically about concepts and situations. It helps student construct their idea in solving mathematics problems. On the other hand, students’ adaptive reasoning still needs to be developed. This is a qualitative study with a case study design. This study was carried out to analyze students’ adaptive reasoning in solving Pythagoras Theorem problems based on gender. There were 31 student participants, of which 14 were males and 17 females. They were the second grade of senior high schools in South of Aceh. There were several steps involved in conducting this study, such as formulating and validating the problems, conducting the test, and interviewing. The problems were formulated based on the adaptive reasoning indicators and curriculum. They were then validated by two lecturers and a teacher. Furthermore, the test was carried out for 20 minutes for answering 4 problems. This study showed that female students were able to solve adaptive reasoning problems as compared to male students. Keywords: adaptive reasoning, gender, solving Pythagoras theorem problems